The Effectiveness of School Resource Management in Improving the Quality of Education - Sherwina Ranisa; Noor Hariani; Ulfia Nurul Anisa; Aslamiah; Ahmad Suriansyah (Universitas Djuanda, 2026)
This study aims to analyze the effectiveness of school resource management, particularly human resources (HR) and financial management, in improving education quality at SMP Negeri 27 Banjarmasin. This research employed a qualitative descriptive approach using the interactive analysis model which includes three main components: data condensation, data display, and conclusion drawing/verification. Data were collected through in-depth interviews, observation, and documentation, while data validity was tested using source and method triangulation. The results indicate that the effectiveness of HR and financial management operates synergistically and integratively. The principal plays a central role in balancing teacher capacity development, budget transparency, and funding priorities for quality improvement activities. The involvement of the school committee and external stakeholders, such as alumni and local businesses, enhances public accountability and broadens resource support. The synergy between professional HR, transparent financial systems, and participatory leadership fosters an adaptive, sustainable, and quality-oriented school management system. These findings highlight that effective resource management is a key factor in building excellent, competitive, and future-responsive schools.